DEMENTIA FRIENDLY NEVADA STATEWIDE COMMUNITY ASSESSMENT: ATTITUDES TOWARD DEMENTIA. (16th November 2018) - Reed, P; Gibb, Z; Carson, J
Abstract: Through 'Dementia Friendly America', communities nationwide are creating strategies to ensure community members living with dementia remain respected and engaged citizens with equal access to everything the community has to offer. With funding from the Administration for Community Living, and under the leadership of the Nevada Aging and Disability Services Division, Nevada has fully embraced these goals. The state has launched six community action groups (CAGs) in a collaborative, participatory action research process to pursue community-specific activities to promote 'dementia friendly communities'. Each community completed a dementia-specific community needs assessment, with an objective to gauge current attitudes toward dementia. Attitudes were assessed using the Dementia Attitudes Scale (DAS) (O'Connor and McFadden, 2010), a validated, 20-item measure of an individual's overall attitude toward dementia, with a total score ranging from 20 – 140. This scale includes two sub-scales: 'social comfort' (range: 12 – 84) and 'dementia knowledge' (range: 8 – 56). Using a snowball sampling strategy, each CAG disseminated the survey as widely as possible to community members between September 2017 and July 2018. A total of 1, 068 Nevadans completed the DAS, with an overall mean score of 105; a mean 'comfort' score of 60; and a mean 'knowledge' score of 45. The results demonstrate a moderately positive attitude toward dementia, yet still offer opportunities for improvement. These data, along with data on community strengths and gaps, were used to develop community action goals, which are now being implemented to shape more inclusive communities for people living with dementia in Nevada.